2015
DOI: 10.15640/jibf.v3n2a6
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ Perception of Non-interest Banking Services by Deposit Money Banks: Evidence fromNigeria

Abstract: This paper examined customers' perception towards non-interest banking services of deposit money banks in Jimeta, Adamawa state, Nigeria. The study sought to examine whether knowledge influences the perception of customers towards non-interest banking services of Deposit Money Banks (DMBs) in Jimeta metropolis, Adamawa state and determine whether there are differences in perception of customers towards Non-Interest Banking Services (NIBS) based on gender, educational qualification and religion. The study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…There has been a considerable increase in IB and finance literature in recent times by scholars and practitioners. While much of the literature on IB is limited to Islam-dominated or Islamic countries (Amin et al, 2011;Echchabi and Nafiu Olaniyi, 2012;Kaabachi and Obeid, 2016;Loo, 2010;Souiden and Rani, 2015), very little research attention has been given to IB in the SSA context (Danjuma et al, 2015;Jinjiri Ringim, 2014). IB was unheard of in non-Muslim countries, and it was considered a wishful thinking by those who desired to engage in banking that was in accord with Islamic principles.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a considerable increase in IB and finance literature in recent times by scholars and practitioners. While much of the literature on IB is limited to Islam-dominated or Islamic countries (Amin et al, 2011;Echchabi and Nafiu Olaniyi, 2012;Kaabachi and Obeid, 2016;Loo, 2010;Souiden and Rani, 2015), very little research attention has been given to IB in the SSA context (Danjuma et al, 2015;Jinjiri Ringim, 2014). IB was unheard of in non-Muslim countries, and it was considered a wishful thinking by those who desired to engage in banking that was in accord with Islamic principles.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that, much of the literature on IB is limited to Islam dominated or Islamic countries (Iqbal and Molyneux, 2006;Manzoor and Amanaullah, 2010;Echchabi and Abdul-Aziz, 2012). Few studies have examined customer perception of IB in Sub-Saharan Africa context (Danjuma et al, 2015;Fada and Wabekwa, JIABR 9,3 2012;Jinjiri, 2014). As a result, there is very limited research on IB in non-Islamic countries such as Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Islamic banking in Nigeria is becoming household name (Danjuma et al , 2015). Hence, Garba (2014) argues that Islamic bank operators should emphasise on justice, equality, trust, honesty, non-prejudice, mutual gain, non-wastage and fulfilling of responsibility as the matters that must be adhered to gain customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, Islamic bank is almost in all geopolitical zones but in few states of Nigeria (Jaizbank, 2015; Ezeh and Nkamnebe, 2019). Specifically, Islamic banking is somewhat gaining prominence in northern Nigeria (Danjuma et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation